(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The performances which are performed by the performer and the Acheivements called its Milestones of a particular Musician. As for as my article is concerned it is based on the Acheavement list of the renowned vocalist of Dr. Gangubai Hangal.as she performed not only in India but in entire world, Her greatest privilege was that despite his performance in the whole world, she never left his place of birth Dharwad Hubli Because of that, she used to call the entire Dharwad by the name of“Ajji”, which means grandmother. I have received a list of Acheavement from different sources like from her birth place Hubli Dharwad, All India Radio Dharwad,Sangeet Natak Academy, and through some literature which I mentioned in bibliography. As a student of vocal music, I have always been of the review that musical vocalists have always deep impression over the history of music in any region. It is the matter of great satisfaction and pride that the region of the Indian subcontinent has witnessed many permutation and combination with regard to vocal music. From the very outside of the history of our music we find that our vocalists showed a keen desire to promote and preserve the vocal faculties of our music. As for as my research article is concerned I have always been interest in the research on the Biography of renowned vocalist Dr. Gangubai hangal was the great vocalist of kirana Gharna and I thought this topic is very relevant and connected with aspiration, and as well as expectation of all persons who wants to know more and more knowledge about the Dr. Gangubai hangal and also who likes to be in pursuance of a career in the field of vocal music. Dr. Gangubai hangal carried deep reverence for the knowledge that was passed on by the guru .Gangubai hangal never found the need to introduce any frills in her music. She sang the truth, as it appeared to her, and that was Gangubai’s virtuosity.